THE IMPACT OF ENTREPRENEURSHIP EDUCATION, EMOTIONAL QUOTIENT AND PARENTAL SUPPORT ON STUDENTS' ENTREPRENEURIAL INTEREST - Kumala Dewi, Fitrika; Yulastri , Asmar; Jalinus , Nizwardi; Ganefri; Mardizal, Jonni (Universitas Muhammadiyah Surakarta, 2024)
Several previous studies have established that entrepreneurship education has an essential effect on students' entrepreneurial interests. However, studies that combine entrepreneurship education, emotional quotient, and parental are still rare. Therefore, this study aims to inform whether there is a potential impact of entrepreneurship education, emotional quotient, and parental support on students' enthusiasm in entrepreneurship at university. A quantitative approach with correlational was employed in this study. The population is all students at Padang State University who are part of the entrepreneurship organization. The sample for this research is students who have taken entrepreneurship courses using a purposive sampling technique, totaling 138 respondents. Data was obtained from the results of the google form questionnaires. The following data analysis stage used SPSS v.22 to analyze the relationship between variables with multiple regression analysis. The analysis results show that there is a positive and significant relationship between entrepreneurship education and students' interest in entrepreneurship, there is a positive and significant impact between emotional quotient toward students' interest in entrepreneurs, and there is a positive and significant relationship between parental support on students' entrepreneurial interest.